Drug Prescriptions during Pregnancy in Lombardy: Temporal Trends and the Impact of the Onset of the COVID-19 Pandemic - Giovanna Esposito; Anna Cantarutti; Matteo Franchi; Giovanni Corrao; Fabio Parazzini (MDPI AG, 2023)
This population-based study aimed at providing an overview of drug prescription patterns during pregnancy in the Italian region of Lombardy from 2010 to 2020. The cohort consisted of 780,075 deliveries identified from the regional healthcare utilization databases. The prevalence of drugs' dispensed prescriptions was estimated as the proportion of pregnant women with at least one prescription out of the total deliveries over the entire pregnancy and by trimester. Drugs were classified according to the Anatomical Therapeutic Chemical code. In addition, interrupted time series analysis was conducted to investigate temporal trends of antibiotics' use during the onset of the COVID-19 pandemic. A total of 497,515 women (63.8%) used at least a drug, including vitamins and minerals, at some point during pregnancy. Vitamins, minerals, and anti-anaemic preparations were prescribed in 20.8%, 13.3%, and 18.3% of deliveries over the trimesters of pregnancy. Folic acid was the most prescribed drug, with about one woman out of four, followed by iron preparations, progestogen, and antibiotics (prescription rate, respectively: 15.9%, 10.2%, and 9.8%). A decreasing trend in the dispensing of antibiotics emerged during the entire study period; however, a significant further decrease following the spread of the pandemic was observed. Further evidence is needed to monitor the use of drugs during pregnancy, determinants, and implications.